Anaerobic Oxidation of Methane at a Marine Methane Seep in a Forearc Sediment Basin off Sumatra, Indian Ocean - Siegert, Michael; Krüger, Martin; Teichert, Barbara; Wiedicke, Michael; Schippers, Axel (Frontiers in Microbiology, 2011)
A cold methane-seep was discovered in a forearc sediment basin off the island Sumatra, exhibiting a methane-seep adapted microbial community. A defined seep centre of activity, like in mud volcanoes, was not discovered. The seep area was rather characterized by a patchy distribution of active spots. The relevance of AOM was reflected by 13C depleted isotopic signatures of dissolved inorganic carbon (DIC). The anaerobic conversion of methane to CO2 was confirmed in a 13C-labelling experiment. Methane fuelled a vital microbial and invertebrate community which was reflected in cell numbers of up to 4 x 109 cells cm 3 sediment and 13C depleted guts of crabs populating the seep area. The microbial community was analysed by total cell counting, catalyzed reporter deposition – fluorescence in situ hybridisation (CARD-FISH), quantitative real-time PCR (qPCR) and denaturing gradient gel electrophoresis (DGGE). CARD-FISH cell counts and qPCR measurements showed the presence of Bacteria and Archaea, but only small numbers of Eukarya. The archaeal community comprised largely members of ANME-1 and ANME-2. Furthermore, members of the Crenarchaeota were frequently detected in the DGGE analysis. Three major bacterial phylogenetic groups (δ-Proteobacteria, candidate division OP9 and Anaerolineaceae) were abundant across the study area. Several of these sequences were closely related to the genus Desulfococcus of the family Desulfobacteraceae, which is in good agreement with previously described AOM sites. In conclusion, the majority of the microbial community at the seep consisted of AOM related microorganisms, while the relevance of higher hydrocarbons as microbial substrates was negligible.